CT-guided sacroiliac percutaneous screw placement in unstable posterior pelvic ring injuries: Accuracy of screw position, injury reduction and complications in 71 patients with 136 screws. Issue 2 (February 2015) - Pieske, Oliver; Landersdorfer, Christoph; Trumm, Christoph; Greiner, Axel; Wallmichrath, Jens; Gottschalk, Oliver; Rubenbauer, Bianka
Abstract Background Sacroiliac-percutaneous-screw-placement (SPSP) for unstable-posterior-pelvic-ring-injuries (UPPRI) might be associated with severe neurovascular complications because of screw-mal-position. The aim of the present study was to analysis the effectivity of computer-tomography-guided (CTG)-SPSP including accuracy of screw-placement, quality of injury-reduction and documentation of perioperative-complications. Additionally, procedure-dependent radiation-dose and outcome should be analysed. Methods A consecutive cohort of 71 patients with UPPRI was operated by CTG-SPSP at a single trauma level 1 hospital. 136 sacroiliac screws were inserted to S1 and S2. Postoperatively, by the use of a computerised-radiologic-work-station all screws were visualised three-dimensionally. Their distancesmin to the sacral-borders in anterior-posterior and cranio-caudal direction as well as to the neuroforamen S1/S2 were determined. After CTG-SPSP, injury-dislocation in anterior-posterior and cranio-caudal direction was quantified. Local and general complications were documented during the 30-day-period. In 55 patients (77.5%) a follow-up-investigation (29.1 ± 19.1 months) was performed. Results 132 screws (97.1%) were placed completely intraosseous, 3 screws (2.2%) perforated up to 1.0 mm (n(S1) = one screw; n(S2) = two screws), and one screw (0.7%) extended 2.2 mm into the S2-neuroforamen without contact to neural structures. Postoperative dislocationanterior-posterior was 1.3 ± 0.9 mm and dislocationcranio-caudal 1.5 ± 0.9 mm. No procedure-associated-complication was observed. Operation time showed a significant "learning curve" during the six-year study period (initially: 88.6 ± 60.3 min; finally: 44.3 ± 24.6 min). Perioperative effective-radiation-dose for patientsmale was 5.9 ± 3.1 mSv and for patientsfemale 8.7 ± 4.5 mSv. All injuries healed and 33 patients (46.5%) had metal removal after 11.0 (±4.9) months. Only two (5.0%) out of 40 patients complained persistent UPPRI-related pain so they were not able to restart work. Conclusions The CTG-SPSP is a safe procedure for UPPRI-stabilisation especially in S1 but also in S2. Injury reduction was excellent and no procedure associated complications were observed.